PERANAN CAMAT DALAM MEMBINA BADAN PERMUSYAWARATAN DESA DIKECAMATAN UJUNG BATU KABUPATEN ROKAN HULU - Susanti, Delpi; Nazir, Yendri (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2015)
This study aims to determine the role of Head in Foster Village Consultative Body in District Ujung Batu Rokan Hulu. Indicator ratings Village Consultative Body builder used includes providing guidance, mentoring, provision of training, referrals, and surpervisi. This type of research beralokasi Ujung Batu sub-district office are descriptive survey, which prioritize the list of questionnaires as a means of data collection and data collected by the tool used as raw material for the empirical conditions in the objectivity of research goals at the location studied. There are two groups of the population and sample in this research that the district governments amounted to four (two) people, the village government amounted to 16 (sixteen), in this case the Village Consultative Body and the Village Head ushered second village in the district of Ujung Batu. The type and data measurement techniques consist of primary data was collected by using a list of questionnaires and interviews as well as a list of secondary data collected by using observation. While data analysis techniques used by the tool table. Based on this technique researchers assess and conclude that the role of Head in Foster Village Consultative Body in District Ujung Batu Rokan Hulu is in the interval Less Good.